Analisis Kepuasan Konsumen terhadap Minuman Jahe Merah (Jahrah) di Cafe Negeri Nikmat (CNN) Kecamatan Sambas - Sunardi; Fia, Misha Khusnul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Consumers have many considerations when choosing to buy a product, paying attention to product quality, service quality, and price quality because these factors are part of consumer satisfaction. The purpose of this study is to determine consumer satisfaction with red ginger products. This study was conducted from February to April 2025 at Cafe Negeri Nikmat (CNN) Sambas. The basic method of this study uses a qualitative descriptive methodology where the data used in this study are primary data and secondary data collected from 100 respondents. The results of this study indicate that product quality with a total of 3270 and a percentage of 82% is stated to be very satisfied by consumers, service quality with a total of 3264 and a percentage of 82% is stated to be very satisfied by consumers, and price quality with a percentage of 3285 and a percentage of 82% is stated to be very satisfied. Overall, the level of consumer satisfaction with red ginger drinks at Cafe Negeri Nikmat is in the very satisfied category. This reflects that this product has succeeded in meeting consumer expectations in terms of quality, service, and price, and has the potential to encourage repeat purchases and consumer loyalty.